2020
DOI: 10.7554/elife.57148
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic encoding of social threat and spatial context in the hypothalamus

Abstract: Social aggression and avoidance are defensive behaviors expressed by territorial animals in a manner appropriate to spatial context and experience. The ventromedial hypothalamus controls both social aggression and avoidance, suggesting that it may encode a general internal state of threat modulated by space and experience. Here, we show that neurons in the mouse ventromedial hypothalamus are activated both by the presence of a social threat as well as by a chamber where social defeat previously occurred. Moreo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…A potential role for VMHdm in encoding defensive motivation is also supported by analogy with single unit electrophysiological recordings and calcium imaging in the ventrolateral division of the VMH (VMHvl), a part of the medial hypothalamic reproductive system, in male mice exhibiting aggression toward male intruders (Lin et al, 2011;Falkner et al, 2014Falkner et al, , 2016Remedios et al, 2017;Krzywkowski et al, 2020). In these studies, VMHvl neurons showed increased firing when exposed to awake males, anesthetized males, or male urine, and the intensity of activation was correlated with the latency and duration of future attacks, demonstrating the encoding of both sensory as well as motivational features of the behavior.…”
Section: Introductionmentioning
confidence: 98%
“…A potential role for VMHdm in encoding defensive motivation is also supported by analogy with single unit electrophysiological recordings and calcium imaging in the ventrolateral division of the VMH (VMHvl), a part of the medial hypothalamic reproductive system, in male mice exhibiting aggression toward male intruders (Lin et al, 2011;Falkner et al, 2014Falkner et al, , 2016Remedios et al, 2017;Krzywkowski et al, 2020). In these studies, VMHvl neurons showed increased firing when exposed to awake males, anesthetized males, or male urine, and the intensity of activation was correlated with the latency and duration of future attacks, demonstrating the encoding of both sensory as well as motivational features of the behavior.…”
Section: Introductionmentioning
confidence: 98%
“…Our findings have two important implications for our understanding of fear in humans. First, our discovery makes it likely that the medial hypothalamus plays a similar role in encoding an internal state of threat in primates as it does in rodents (Kunwar 2015 ; Silva et al 2016a ; Esteban Masferrer et al 2018 ; Krzywkowski et al 2019 ; Masferrer et al 2018 ; Kennedy et al 2019 ). Notably, VMHdm in rodents is required for the induction and expression of both innate and conditioned predator fear (Silva et al 2013 , 2016 ; Kunwar 2015 ) and stimulation of VMHdm in monkeys and humans is sufficient to elicit an intense defensive emotional state (Wilent 2010 ; Lipp and Hunsperger 1978 ).…”
Section: Discussionmentioning
confidence: 97%
“…Finally, we ran the simulations to fit the experimental data. We observed that, to reproduce the experiment of Krzywkowski et al (2020), the connection between vHIP and VMHvl had to be made plastic. This corresponds to a principle of parsimony aimed at simplifying the model, staying as much as possible grounded on literature, and minimizing the hypothesis.…”
Section: Synaptic Plasticitymentioning
confidence: 95%
“…This led to a more powerful activation of the Pyr2 fear-OFF population, compared to the non manipulated control, and to a consequent deactivation of the Pyr1 fear-ON population (Figures 5D,E). Krzywkowski et al (2020) studied the activation of different VMHvl populations during the aversive social encounter and when the mice were re-exposed to the same context without the opponent. Their Defeat+ population corresponds to our threat unit Hyp1, which is active during, but not before, conditioning (Figure 5F; see also Figure 2B).…”
Section: Reproduction Of Key Target Experimentsmentioning
confidence: 99%
See 1 more Smart Citation